Combined electrolytic iron dissolution and ozonation process for arsenic removal from water - Roberto Contreras-Bustos; María Elena Quezada González; Bibiana Cercado; Jaime Jiménez-Becerril; Marcos J. Solache-Ríos (Desalination and Water Treatment, 2024)
In some regions, underground water contains dissolved arsenic and this is a health risk for the population. In this work, arsenic was reduced to acceptable levels. Water from Zacatecas, Mexico, containing 1.58, 1.72 and 2.03 mg/L of As, Fe and Mn respectively, and pH 2.0, was treated with Fe from electrolytic dissolution, then with a mixture of ozone and air. The parameters considered during the treatment were agitation rate, ozone flux, pH, temperature, and dissolution time of iron. The concentration of As was reduced by co-precipitation with Fe from the electrolytic dissolution and by co-precipitation with Mn contained in the water when ozone was injected. The results indicated that the co-precipitation reactions depended on the mass transport. The ozone oxidizes the Mn in two steps (pH 2): firstly, the Mn (II) is oxidized to Mn (IV) and precipitated and secondly, the precipitated Mn (IV) is oxidized and dissolved as Mn (VII). Arsenic co-precipitated in the first Mn oxidation step, and then it turned into a solution together with the Mn at high flow of ozone. The residual concentrations of Fe, Mn and As in the water at pH 7 are 0.014, 0.07 and 0.00512 mg/L, respectively.